Gross motor development of children with autism spectrum disorder aged 6-10 years and typically developed children - Kurniawan, Rama; AdiLuhung, Galas Seto Rega; Kusumasari, Herdika Ayu Retno (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2025)
Developmental disorders in autistic children are one of the problems that require early detection so that developmental deviations do not occur. This study aims to determine the gross motor conditions of autistic students and children developing at the same age using the TGMD-2 (Test of Gross Motor Development-2) instrument.(Ulrich, 2000). This study uses a quantitative approach using a survey method. Sampling used with purposive sampling technique through certain considerations including age and demographic conditions of the same area. The sample in this study consisted of 10 SLB students and 17 regular students with data analysis techniques in this study using quantitative descriptive. The results of this study indicate that autistic children have a